Peran Pembelajaran Al-Qur'an dan Hadis dalam Pembinaan Akhlak Karimah Siswa MA Rohani Ikhwanul Muslimin - Rosdiana, Rosdiana; Setiawan, Hasrian Rudi (EL-EMIR Institute, 2025)
The learning of the Qur’an and Hadith plays an important role in shaping students’ noble character (akhlaq karimah). This study aims to analyze the implementation of Qur’an and Hadith learning at MA Rohani Ikhwanul Muslimin in fostering students’ character development. The method used is Classroom Action Research (CAR) with the Kemmis & McTaggart model through the stages of planning, action, observation, and reflection. Data were collected through observation, interviews, and documentation, then analyzed qualitatively using data reduction, data presentation, and conclusion drawing. The results showed that learning strategies combining intracurricular activities, daily worship practices, and religious extracurricular activities were effective in fostering students’ honesty, discipline, tolerance, and social awareness. This success was supported by teachers’ role modeling, the integration of moral values into the curriculum, and a religious school culture, although there were still obstacles such as limited time, family background, and the influence of social media. In conclusion, Qur’an and Hadith learning not only serves as a transfer of knowledge but also as a strategic instrument in shaping students’ noble character to face modern challenges based on Islamic values.